Preservice Psychology Training About (Specific) Learning Differences. (20th September 2018) - Sadusky, Andrea; Freeman, Nerelie C.; Jacobs, Kate E.; Reupert, Andrea E.
Abstract : What Australian psychologists currently learn about specific learning disorders (SLDs) through postgraduate-level training is not clear. Accordingly, the current Australia-wide study analysed 800 postgraduate psychology unit handbook entries to identify which courses teach about SLD and what they teach in this area. Only 2.38% of the identified units explicitly indicated SLD-related content, with 0.38% solely dedicated to SLD content. Descriptive analyses revealed differences in labels used for SLD. Thematic analyses identified five areas of knowledge and skills across SLD units including assessment, intervention, theory and empirical evidence, developmental and cultural awareness and sensitivity, and interpersonal communication. The present findings can inform future refinements to university-level psychology programs across Australia by highlighting the gaps and needs in psychology training.